2003
DOI: 10.1056/nejmoa032312
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Letrozole in Postmenopausal Women after Five Years of Tamoxifen Therapy for Early-Stage Breast Cancer

Abstract: As compared with placebo, letrozole therapy after the completion of standard tamoxifen treatment significantly improves disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
873
1
40

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,677 publications
(926 citation statements)
references
References 35 publications
12
873
1
40
Order By: Relevance
“…These tumors are therefore useful for studying and comparing the effects of both antiestrogens (AEs) and AIs in the same model system (Yue et al 1994). Clinical trials (BIG 1-98, ATAC, MA-17) have now confirmed the results of our xenograft model (Baum et al 2002, Goss et al 2003, 2005, Thurlimann et al 2005, Goss 2006 …”
Section: Discussionsupporting
confidence: 78%
“…These tumors are therefore useful for studying and comparing the effects of both antiestrogens (AEs) and AIs in the same model system (Yue et al 1994). Clinical trials (BIG 1-98, ATAC, MA-17) have now confirmed the results of our xenograft model (Baum et al 2002, Goss et al 2003, 2005, Thurlimann et al 2005, Goss 2006 …”
Section: Discussionsupporting
confidence: 78%
“…Newer therapies targeting ER via different mechanisms, such as aromatase inhibitors (AI; Goss et al 2003) and selective ER downregulators (e.g. ICI182780; Robertson 2002), or potential new therapies, such as electrophilic modulators of ER zinc fingers (Wang et al 2004), were all developed from basic research into molecular mechanisms of ER action, but development of therapy resistance is likely also to be a problem clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Only in 2003(the year SOFT and TEXT started accrual) were the results of MA.17 published showing that an AI(letrozole) after 5 years of TAM reduced DFS events in postmenopausal women with resected breast cancer [17]. Even then, there was a concern that patients premenopausal at diagnosis who lost ovarian function before the 5-year point would not benefit from further decreases in estrogen levels induced by blockade of aromatase.…”
Section: The Analysis Ignored the Efficacy Of Endocrine Therapy Aftermentioning
confidence: 99%
“…This treatment suffers from a paucity of data showing that further endocrine therapy is effective after 5 years of an AI. In contrast, we know that more TAM improves survival after 5 years of TAM [18,19], and an AI improves DFS after 5 years of TAM [9,17]. By the end of 2016, one study had been published [20] and 3 more had been presented at the 2016 San Antonio Breast Cancer symposium showing little or no benefit for extending AI therapy beyond 5 years except for continued suppression of new contralateral breast cancers [21][22][23].…”
Section: Little Benefit From Hormonal Therapy After Ai For 5 Yearsmentioning
confidence: 99%